Evaluasi Ketaatan dan Transparansi Pelaporan Dana Kampanye Pemilihan Presiden 2019 - Hamdani Hamdani (Jurnal Eksplorasi Akuntansi, 2024)
In accordance with KPU Regulation Number 3 of 2022, campaign activities for the 2024 presidential election will begin on November 28 2023. The KPU sets administrative requirements regarding campaign funds that must be complied with by all election contestants, including presidential and vice presidential candidate pairs. This research is intended to evaluate compliance and transparency in reporting campaign funds for the 2019 presidential election with the aim of measuring compliance and transparency in reporting campaign funds for the 2019 presidential election which can be used as a benchmark for managing campaign funds in the 2024 presidential election. The results of the research show that several complete accountability forms were not made, and deposits were not made. recorded at the LPPDK, did not create a separate list of donors that did not include identification, reporting of TPS witness funds was not transparent, there were allegations that donations were used outside of campaign funding purposes, and PKPU had not clearly regulated a tiered accountability mechanism. There are difficulties in implementing PKPU Number 24 of 2018 concerning General Election Campaign Funds because reporting is not carried out in stages from district/city to province and center, but the report format is presented according to election administration areas. However, accountability and bookkeeping are carried out centrally by the national campaign team, where revenue and expenditure traffic goes through the RKDK.